Back to basics: A role of reading, writing, and arithmetic teaching - Alghazo, Ali M.; Abdelhamid, Sherif; Alghazo, Runna (Frontiers in Education, 2022)
This study has assessed the role of reading, writing, and arithmetic teaching among adult learners in Saudi Arabia. A quantitative approach was used by recruiting 186 students divided into three groups, i.e., WTL (write to learn) group, traditional teaching group, and ITU group (Individual technology use). SPSS was used for the analysis of the arithmetic and literacy test scores of the students. The findings showed that WTL group performance was most effective among the three groups. The results showed that the learning capacity of adults could be improved by refining the writing and reading skills. The formative feedback, collaborative environment, and engagement helped improve the learning scores. It shows that the use of ICT (Information and Communication Technology) should be accurately implemented along with the formation of a collaborative environment